2014
DOI: 10.1038/srep05468
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomal effect of space flight-associated microgravity on stress-activated protein kinases in innate immunity

Abstract: Space flight strongly moderates human immunity but is in general well tolerated. Elucidation of the mechanisms by which zero gravity interacts with human immunity may provide clues for developing rational avenues to deal with exaggerated immune responses, e.g. as in autoimmune disease. Using two sounding rockets and one manned Soyuz launch, the influence of space flight on immunological signal transduction provoked by lipopolysaccharide (LPS) stimulation was investigated in freshly isolated peripheral blood mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…As taSMG can be achieved artificially, studies using this technique have advanced rapidly. Based on symptoms experienced by astronauts in the space such as muscle atrophy, bone loss, and immunodeficiency, microgravity has been investigated in the treatment of various diseases 2 , 4 , 6 , 7 , 10 , 17 . Our research team designed a clinostat that uses a specific algorithm aimed at randomizing the gravitational vector pattern and achieving a nullified time-averaged vector 46 .…”
Section: Discussionmentioning
confidence: 99%
“…As taSMG can be achieved artificially, studies using this technique have advanced rapidly. Based on symptoms experienced by astronauts in the space such as muscle atrophy, bone loss, and immunodeficiency, microgravity has been investigated in the treatment of various diseases 2 , 4 , 6 , 7 , 10 , 17 . Our research team designed a clinostat that uses a specific algorithm aimed at randomizing the gravitational vector pattern and achieving a nullified time-averaged vector 46 .…”
Section: Discussionmentioning
confidence: 99%
“…This analysis showed the presence of several signatures of autoimmune repression ( Table 1 ), which were never reported. A recent study speculated microgravity could be a measure for fighting autoimmune disease 9 . Further, tissue engineering model in microgravity showed the enhanced survival, better secretory profile and better insulin normalization of beta islet cells compare to ground control 42 .…”
Section: Discussionmentioning
confidence: 99%
“…During today’s space missions, a short to moderate microgravity exposure (days to months) induces several physiological changes in human body including bone and muscle loss, puffiness in the face, change in cardiovascular physiology, catecholamine cardiomyopathy, insufficient blood flow in the brain, genitourinary issues and disturbance in neurovestibular system 2 3 4 5 6 7 . Further, microgravity induces deregulation of human immune systems 8 9 . Multiple gene expression studies showed microgravity-induced signature of early inhibition in T cell activation 10 , impaired endothelial cell function 11 , cellular senescence 12 , alteration of genes related to cell cycle 13 14 , cell adhesion 11 , oxidative phosphorylation 14 and apoptosis 14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This ultra-low range and sensitive space accelerometer will undergo a series of ground-based pre-flight experiments to verify its function and performance. Currently, various facilities are available to perform microgravity experiments near the ground, such as drop towers or drop wells, parabolic flights, balloon-drops and sounding rockets 7 8 9 . The small residual gravity, low cost and high throughput of experiments 10 make the drop tower become an ideal choice for our ground-based test.…”
mentioning
confidence: 99%